Towards a Policy Framework for The Use of Generative AI in Nigerian Curriculum For Early Childhood Education - Aliyu, Aliyu Yaya (CV Media Inti Teknologi, 2025)
Background of Study: The integration of artificial intelligence (AI)—particularly generative AI (GenAI)—into early childhood education (ECE) is rapidly advancing. While it presents transformative opportunities for learning and teaching, it also raises significant ethical, regulatory, and humanistic concerns. The accelerated development of GenAI tools often outpaces the establishment of appropriate educational safeguards and policy responses. Aims and Scope of Paper: This study investigates the implications of GenAI on fundamental humanistic principles in ECE, specifically focusing on inclusivity, equity, and human agency. It aims to assess how current regulatory and institutional frameworks address the risks and responsibilities associated with GenAI in early learning environments. Methods: A qualitative methodology was employed, incorporating policy analysis and semi-structured interviews with experts in education, ethics, and technology. This approach was used to evaluate both the current state of national regulations and the readiness of educational institutions to manage GenAI integration responsibly. Result: The study found a significant misalignment between the rapid technological evolution of GenAI and the slow pace of regulatory adaptation across most countries. There is a widespread absence of clear, actionable guidelines regarding data privacy, ethical use, and accountability within educational contexts, especially for early learners. Conclusion: Without timely and thoughtful policy interventions, the adoption of GenAI in ECE may inadvertently erode core values that support equitable and inclusive education. The paper recommends that governments and institutions develop comprehensive policy frameworks, implement robust data governance mechanisms, and revise existing AI regulations to better address the unique challenges posed by GenAI in early childhood learning.